Self-Regulation of Learning: An Experience of Teacher Mediation in Hybrid and Online Environments (Educational Knowledge, 2024)
The primary objective of this research is to systematically scrutinize the nuanced facets of teacher mediation within the context of high school students’ self-regulated learning, specifically in the domain of mathematics, within hybrid and online learning environments. A total cohort of 183 students actively participated in this study, with 87 engaged in an online learning setting and 96 in a hybrid educational milieu. Employing a rigorous quantitative methodology, two discerning instruments, namely the Teacher Support Questionnaire and a segment of the Student Satisfaction Survey evaluating the Teaching Quality of the faculty, were methodically applied.The obtained results reveal a pervasive perception among students in both online and hybrid environments, wherein a heightened level of pedagogical expertise is discerned relative to the teacher’s facilitation of self-regulated learning. Noteworthy among the esteemed mediation characteristics, students particularly emphasize the provision of targeted exercises to fortify their learning experience, along with the reception of warm and respectful interactions from their educators.These empirical findings conclusively affirm the imperative to champion the cultivation of self-regulation strategies, underscoring their pivotal role in augmenting academic proficiency in the domain of mathematics at the secondary education level. This study contributes substantively to the discourse on educational methodologies, emphasizing the symbiotic relationship between teacher mediation and the cultivation of effective self-regulation strategies for enhanced academic outcomes in secondary education mathematics.
Keywords: Teacher mediation; Self-regulated learning; Mathematics education; Hybrid learning environments; Pedagogical expertise